2016
DOI: 10.4081/aiua.2016.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines for urinary stone treatment. A systematic review

Abstract: Citrate is more effective than phytotherapy in decreasing the size of existing calculi in the urinary tract and in decreasing the urinary excretion rate of uric acid. A preparation containing Didymocarpus pedicellata combined with other herbal agents induces stone size reduction and clearance significantly better than placebo. Mayor limitations in the applicability of these results are the low quality of the evidence and the multiple sources of bias assessed in the studies included in the present review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Thus, this lack of information is a limitation of the knowledge of the mechanism of action of these medicinal plants. The presence of several bioactive compounds in these plants may be responsible for their beneficial effects [ 34 , 61 ]. A few of the main compounds contained in their chemical composition are flavonoids, phytosterols, saponins, furanochromones, alkaloids, and terpenoids.…”
Section: Molecular Mechanism Of Bioactive Compounds Present In Medici...mentioning
confidence: 99%
“…Thus, this lack of information is a limitation of the knowledge of the mechanism of action of these medicinal plants. The presence of several bioactive compounds in these plants may be responsible for their beneficial effects [ 34 , 61 ]. A few of the main compounds contained in their chemical composition are flavonoids, phytosterols, saponins, furanochromones, alkaloids, and terpenoids.…”
Section: Molecular Mechanism Of Bioactive Compounds Present In Medici...mentioning
confidence: 99%
“…They found that citrate is more effective than phytotherapy in decreasing the size of existing calculi in the urinary tract and in decreasing the urinary excretion rate of uric acid. 27 We previously conducted a pilot study on the use of WLS for calcium oxalate stone prevention. 20 The urine amount was increased slightly in this study, which included a small number of cases with short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…calcium antagonists, N-acetyl-cysteine, and phytopharmaceuticals) could interfere with these mechanisms and lower urinary stone formation 1, 2330 . These observations could open up new options in renal stone prevention and metaphylaxis (secondary prevention) 31 . Standardized preparations like Canephron N containing centaury, lovage, and rosemary exhibit not only anti-oxidative and nephroprotective but also diuretic and anti-inflammatory effects.…”
Section: Understanding Urolithiasismentioning
confidence: 93%